2020
DOI: 10.1200/jco.2020.38.15_suppl.e17563
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcome with abiraterone low-dose plus prednisone in patients with mCRPC in a Brazilian Public Cancer Center.

Abstract: e17563 Background: Abiraterone acetate (AA) is a potent selective and irreversible inhibitor of CYP17 used as standard treatment for metastatic Castration Resistant Prostate Cancer (mCRPC). In the pivotal trial COU-AA 301, AA 1000 mg/day plus prednisone increased overall survival after docetaxel in patients with mCRPC. A recent trial demonstrated not inferiority with respect to PSA metrics in the reduced dose of 250mg/day AA associated with dietary intake, which is described as AA low dose (AALD). The introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…68 The development of this dosing regimen is particularly surprising given the lack of dose-response and marked food effects evident in Cougar's phase I study. 139 More recently, a randomized study demonstrated the apparent equivalence of 250 mg with food (low-fat breakfast) and the labeled dosing regimen, 33 leading to incorporation of this off-label dosing regimen in National Comprehensive Cancer Network guidelines, 140 soon followed by adoption in India, 141 Brazil, 142 and Thailand. 143 Furthermore, given the prolonged effect of a single dose of this irreversible inhibitor, it is likely that a 500-mg dose administered with food every 2 to 7 days may be as effective as the labeled dosing regimen of 1,000 mg once daily on an empty stomach.…”
Section: Abirateronementioning
confidence: 99%
“…68 The development of this dosing regimen is particularly surprising given the lack of dose-response and marked food effects evident in Cougar's phase I study. 139 More recently, a randomized study demonstrated the apparent equivalence of 250 mg with food (low-fat breakfast) and the labeled dosing regimen, 33 leading to incorporation of this off-label dosing regimen in National Comprehensive Cancer Network guidelines, 140 soon followed by adoption in India, 141 Brazil, 142 and Thailand. 143 Furthermore, given the prolonged effect of a single dose of this irreversible inhibitor, it is likely that a 500-mg dose administered with food every 2 to 7 days may be as effective as the labeled dosing regimen of 1,000 mg once daily on an empty stomach.…”
Section: Abirateronementioning
confidence: 99%